2021
DOI: 10.1111/xen.12683
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized xenografts in regenerative medicine: From processing to clinical application

Abstract: Decellularized xenografts are an inherent component of regenerative medicine. Their preserved structure, mechanical integrity and biofunctional composition have well established them in reparative medicine for a diverse range of clinical indications. Nonetheless, their performance is highly influenced by their source (ie species, age, tissue) and processing (ie decellularization, crosslinking, sterilization and preservation), which govern their final characteristics and determine their success or failure for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 375 publications
(218 reference statements)
0
20
0
1
Order By: Relevance
“…Specifically, these structures need to support intrinsic physiological functions, biocompatibility, and somatic growth akin to native tissues and organs (Wang et al, 2022a;Shakeel and Corridon, 2023a). Arguably, some of the most challenging parts of creating viable tissue-engineered xenografts include ensuring that they accurately mimic native tissues and limit immunogenicity (Fishman, 2018;Platt et al, 2018;Capella-Monsonís and Zeugolis, 2021;Wang et al, 2022a;Liu et al, 2022). These features are essential in providing a possible solution to the scarcity of transplantable tissues and organs.…”
Section: Viability and Sustainability Of Xenografts Derived From Slau...mentioning
confidence: 99%
“…Specifically, these structures need to support intrinsic physiological functions, biocompatibility, and somatic growth akin to native tissues and organs (Wang et al, 2022a;Shakeel and Corridon, 2023a). Arguably, some of the most challenging parts of creating viable tissue-engineered xenografts include ensuring that they accurately mimic native tissues and limit immunogenicity (Fishman, 2018;Platt et al, 2018;Capella-Monsonís and Zeugolis, 2021;Wang et al, 2022a;Liu et al, 2022). These features are essential in providing a possible solution to the scarcity of transplantable tissues and organs.…”
Section: Viability and Sustainability Of Xenografts Derived From Slau...mentioning
confidence: 99%
“…Previous studies have shown that, for example, growth factors are retained in tissue grafts 121 and they are also subjected to harsh preparation protocols (e.g., decellularisation, crosslinking, sterilization, and preservation). 122 Further, species-specific peptides have been identified in skinderived samples and gelatin preparations. 123 Also, similarities and differences have been detected in collagen devices produced from porcine peritoneum and skin.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…The first one, should examine in detail the composition of collagen preparations. Previous studies have shown that, for example, growth factors are retained in tissue grafts 121 and they are also subjected to harsh preparation protocols (e.g., decellularisation, crosslinking, sterilization, and preservation) 122 . Further, species‐specific peptides have been identified in skin‐derived samples and gelatin preparations 123 .…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…The most common natural polymers used for collagen membrane fabrication are collagen type I and type III [ 8 ]. Natural collagen is extracted by decellularization and removal of antigenic components from primary sources which include but are not limited to porcine skin, porcine pericardium, and bovine tendon [ 11 , 12 ]. Collagen-based products can be made of either purified collagen after extraction and scaffold fabrication or from decellularization and optional crosslinking where the collagen is not extracted and also keeps the natural 3D microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…A modification by crosslinking improves the mechanical properties of collagen membranes as it can stabilize the collagen matrix and increases resistance to resorption. Different methods can be used to form a crosslinked collagen membrane such as ultraviolet (UV) irradiation and chemical processing [ 11 , 12 , 13 ]. However, the crosslinked collagen membranes and their degradation products can have toxic effects to the surrounding environment which can lead to delayed angiogenesis, insufficient bone regeneration, and interfere with wound healing [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%